Reel Latinxs : Representation in U.S. Film and TV - Aldama, Frederick Luis, 1969-; González, Christopher (Book collections on Project MUSE., 2019)
"This book explores the representations of Latinx in mainstream film and television. The authors provide a roadmap through the history of Latinx misrepresentation, including character types, sexuality, and casting issues, and discuss the disproportionate appearance of Latinx in films and TV despite their growing demographic in the United States"--